Response of common bean genotypes to prevalent Pseudocercospora griseola races causing angular leaf spot in Uganda - Kyomugisha, Prossy; Kato, Fred; Amongi, Winnyfred; Akankunda, Trace; Ssekamate, Male Allan; Mukankusi, Clare M. (African Scholarly Science Communications Trust, 2023)
Angular Leaf Spot (ALS) caused by Pseudocercospora griseola is responsible for 54% yield loss in Uganda’s common beans. Host plant resistance is a safe and cost-effective management strategy for this disease. Identification of resistant common bean genotypes to prevailing races is vital to utilize the crop. Therefore, the objective of this study was to identify genotypes that are resistant to the commonly occurring and virulent P. griseola races in Uganda for breeding purposes. Twenty-seven common bean genotypes and three control varieties (Mexico54, MCM5001, and CAL96) were screened at field conditions for ALS resistance at testing site (National Agricultural Research Laboratories - Kawanda) under natural disease infection. The genotypes were also evaluated in the screen house using frequently occurring P. griseola races: 61:63, 1:6 and 21:39. Variability in the severity of ALS on both leaves and pods was significant whereas the difference between seasons and the interaction between the seasons and genotypes was only significant for yield. The disease severity scores were higher (mean of 3.2) on leaves than on pods (mean of 2.9). Ninety-three percent, 33.3% and 15% of the genotypes were resistant to P. griseola races 21:39, 1:6 and 61:63, respectively. A large-seeded genotype AFR703 was resistant to all the three P. griseola races. A medium seed size genotype AFR702 and three small seed genotypes (G148, G18842 and G6727) were resistant to both 21:39 and 1:6 but moderate resistance to 61:63 whereas a large-seeded genotype AND279 was resistant to both 61:63 and 21:39 but moderate to 1:6. All of these six genotypes (AFR703, AFR702, G148, G18842, G6727 and AND279) expressed moderate resistance to P. griseola races on leaves under field conditions. Thus, these common bean genotypes could be used as sources of ALS resistance for breeding programs to address the ALS constraint; and genes responsible for resistance have to be characterized. Key words: Pathology, Disease, Resistance, Infection, BALSIT, Pathotypes, Prevalent, Races